Characterization of local chicken production systems and their potential under different levels of management practice in Jordan - Abdelqader, A.; Wollny, C.B.A.; Gauly, M. (Springer, 2007)
This study aimed to characterize the local chickens and their production systems and to investigate the opportunities for improvement. The study was carried out in 18 villages in northern Jordan with the participation of 120 households. Data were collected by individual interviews and surveys supported with structured questionnaires. A scoring system was developed to study the effect of different levels of management on chicken performance. The main reasons for keep local chickens were egg production and generation of income. The main features of the production systems were improper housing and inadequate hygiene. Newcastle disease, predators, and parasites were the main causes of flock losses. Purchasing rate was controlled by the chickens' phenotype, sex and age, and by season of year. The average flock size was 41.6 (±32.9) chickens per household, with a hen:cock ratio of 6.4:1. The average effective population size was 15.35, which indicated a high rate of inbreeding (5.52%). The main selection criterion adopted by farmers was egg production. There were positive significant correlations (p<0.001) between management level and chickens' performance. Hatchability, survivability, flock size, number of clutches, egg weight and egg mass were the major parameters that improved significantly with improvement in management level. Local chickens fulfil significant functions in the livelihood of rural smallholders; however, many constraints affected the efficiency of the production systems. Solutions should start with improving the management practices and establishing an effective breeding system. © 2007 Springer Science + Business Media B.V.